Lnc-PLA2G4A-4 facilitates the progression of hepatocellular carcinoma by inducing versican expression via sponging miR-23b-3p - Jiahui Xiong; Yongping Lai; Niangmei Cheng; Jizhe Liu; Fei Wang; Xiaoyuan Zheng; Yingchao Wang; Qiuyu Zhuang; Yantin Lin; Jingfeng Liu; Yixuan Yang; Bixing Zhao; et al. (Heliyon, 2023)
Aberrant expression of long non-coding RNAs (lncRNAs) is associated with progression of multiple human cancers including hepatocellular carcinoma (HCC). However, the role of lncRNAs in HCC is not been fully understood. Our study aimed to investigate the biological function and potential molecular mechanism of Lnc-PAL2G4A-4 in HCC. In the current study, we show that Lnc-PLA2G4A-4 was significantly up-regulated in HCC tissues and high Lnc-PLA2G4A-4 expression was remarkably associated with tumor size, microvascular invasion and poor prognosis of HCC patients. Functionally, Lnc-PLA2G4A-4 positively regulated cell proliferation, invasion and migration in vitro, and facilitated lung metastasis of HCC in vivo. Mechanistically, Lnc-PLA2G4A-4 functioned as a competing endogenous RNA (ceRNA) to bind to miR-23b-3p and subsequently facilitate miR-23b-3p's target gene versican (VCAN) expression in HCC cells. Over-expression of miR-23b-3p could reverse Lnc-PLA2G4A-4 induced cell phenotypes in HCC and suppress versican expression of by rescue analysis. Collectively, Lnc-PLA2G4A-4 promotes HCC progression by targeting the miR-23b-3p/versican axis, which may be a potential biomarker and therapeutic target for HCC.